Studies on Antioxidant Activities of Chemical Constituents of Swertia mussotii Franch - Zhang1, Jian-Sheng; Wang2, Xue-Mei; Gao1, Yun-Tao; Li1, Gan-Peng (Asian Journal of Chemistry, 2011)
To study the chemical constituents in Swertia mussotii Franch and their scavenging effects of active oxygens species. A new xanthone named 1,7-dihydroxy-2,3,8-trimethoxyxanthone (1), together with 1,8-dihydroxy-2,6-dimethoxyxanthone (2) and sweroside 2'-O-(3,3',5- trihydroxy-2-biphenylcarboxylate (3), were isolated from Swertia mussotii Franch. Their structures were elucidated by spectroscopic methods, including one and two-dimensional NMR (COSY, HMQC, HMBC and ROESY). Scavenging effects of them on active oxygen species ·OH and O2 – generated by Fenton reaction and riboflavine photosensitization in vitro were investigated by the means of spectrophotometry for the first time and the results showed that three compounds could scavenge active oxygen species efficiently.